Pengembangan Bahan Ajar Bangun Datar Kelas 4 Pendekatan Open-Ended Untuk Meningkatkan Penalaran Di SD - Hidayah Sri Murwati; Joko Sulianto; Aries Tika Damayani (STKIP Andi Matappa Pangkep, 2022)
The background of this research and development is the teaching materials used in elementary schools haven’t motivated students to learn mathematics, especially those related to teaching materials for flat shapes that can improve students' reasoning based on open-ended approach. The purpose of this study was to determine the availability of teaching materials in elementary schools and steps for developing flat shapes teaching materials to improve reasoning. The type of research used the Research and Development (RnD) Borg and Gall model. The data analysis technique used descriptive qualitative. The results of feasibility assessment material expert validation stage 1 obtained a percentage 51.25% categorized